Efforts to preserve traditional music through social knowledge subjects - Jumriani, Jumriani; Muhaimin, Muhammad; Mutiani, Mutiani; Warmansyah Abbas, Ersis; Rusmaniah, Rusmaniah (Journal of Education and Learning (EduLearn), 2024)
People's lives tend to the outside world, leading to the waning of cultural preservation values due to the ease with which foreign cultural influences enter and threaten the existence of local culture. To avoid the decline of the younger generation's interest in traditional art, it is necessary to carry out an idea of preservation through education, in this case, social studies subjects at school. This study aims to analyze the relationship between traditional art and social studies as a learning resource. The traditional art discussed in this study is panting music which is traditional arts in South Kalimantan. This is done to get a pattern for preserving traditional arts through social studies subjects. The research method used is qualitative. Data collection is done through observation, interviews, and documentation. Informant this research panting music players, and social studies teachers. The various data obtained are then reduced, presented, and then concluded. The researcher triangulated and extended the observations. The study's results confirmed panting music performance activities could be packaged as social studies learning resources. This is done by integrating class VII textbooks on the theme of cultural and ethnic diversity in the Indonesian traditional musical.